KENDALA KEBIJAKAN OTSUS ACEH DITINJAU DARI TEORI GRINDLE POLICY IMPLEMENTATION - Ardiansyah Ardiansyah (Journal of Political Sphere, 2020)
AbstractThe existence of the special autonomy fund should make Aceh an advanced area in terms of development, empowerment of the people's economy, poverty alleviation, health education, and social issues. however, the reality shows a decline in various fields. Data released by the Central Statistics Agency (BPS) shows Aceh is in the second position as the poorest region. Apart from that, in terms of education quality, Aceh is in the 27th position out of 34 provinces. This study aims to analyze the constraints of implementing the policy on the use of special autonomy funds based on the Grindle model review. The methods used are qualitative methods and literature study. Respondents in this study were the special autonomy fund policy makers in Aceh. The results showed that the obstacles that occurred in the management of special autonomy funds were caused by conflicts interest of the elite groups. according to the grindle model theory, there are indicators that are not fulfilled in policy implementation, namely the presence of group elements from policy makers.Keywords:Special Autonomy, Special Autonomy Fund, Policy Implementation